O fechamento do Aterro Metropolitano de Jardim Gramacho no Rio de Janeiro: uma experiência de governança entre trabalhador, empresário e governo - Steinbrück, Melissa Sabbag Abla (2012)
The closure of the operations of Jardim Gramacho Metropolitan Landfill (AMJG) in Duque de Caxias / RJ, brought the opportunity to study the formation and consolidation of a governance structure public-private redevelopment purposes neighborhood. From this case study, this work investigates the factors that facilitate and inhibit the consolidation of territorial governance structure aimed at positive results in the medium and long term. To develop this thesis, it was necessary to demonstrate the effects generated by the absence of metropolitan authorities in solving problems that go beyond the municipal areas and obstacles generated in small municipalities that are required to deal with such situations. The research is based on studies on governance and contextualized from the 1980s, when there was widespread use of large governance towards building democratic and participatory public policy.